Are you sure? a look at uncertainty and media exposure. - Chew, Hui Min. (2008)
This study attempts to fill out the concept of need for orientation - a psychological motive for media expose and agenda-setting effects. Issue uncertainty and issue relevance as well as the personality trait of uncertainty orientation were incorporated to build a model predicting purposive to news and information.